End Overfishing and Increase the Resilience of the Ocean to Climate Change - Sumaila, U. Rashid; Tai, Travis C. (Frontiers in Marine Science, 2020)
Abstract Marine fish stocks and the ecosystems they inhabit are in decline in many parts of our ocean, including in some European waters, because of overfishing and the ecosystem effect of fishing in general. Simultaneously, climate change is disrupting the physics, chemistry and ecology of the ocean, with significant consequences on the life it holds. While the positive effects of mitigating climate change on the ocean and marine life are currently being documented, papers that examine how ending overfishing could increase ocean resilience to climate change are less common. The goal of this paper is to review the current literature and conduct an analysis that demonstrate that ending overfishing and reducing other negative ecosystem effects of fishing would make fish stocks and marine ecosystems more resilient to climate change. Our findings suggest that fish and fish stocks are no different from other living organisms and are more likely to survive external pressures when healthy.